Cooperation between Different Forms of the Human Papillomavirus Type 1 E4 Protein To Block Cell Cycle Progression and Cellular DNA Synthesis - Knight, Gillian L. (American Society for Microbiology, 2004)
Posttranslational modification—oligomerization, phosphorylation, and proteolytic cleavage—of the human papillomavirus (HPV) E4 protein occurs as the infected keratinocytes migrate up through the suprabasal wart layers. It has been postulated that these events modify E4 function during the virus life cycle. In HPV type 1 (HPV1)-induced warts, N-terminal sequences are progressively cleaved from the full-length E4 protein (E1(∧)E4) of 17 kDa to produce a series of polypeptides of 16, 11 and 10 kDa. Here, we have shown that in human keratinocytes, a truncated protein (E4-16K), equivalent to the 16-kDa species, mediated a G(2) arrest in the cell cycle that was dependent on a threonine amino acid in a proline-rich domain of the protein. Reconstitution of cyclin B1 expression in E4-16K cells reversed the G(2) arrest. Expression of E4-16K also induced chromosomal rereplication, and this was associated with aberrant nuclear morphology. Perturbation of the mitotic cell cycle was a biological activity specific to the truncated protein. However, coexpression of the full-length E1(∧)E4 protein and the truncated E4-16K protein inhibited normal cellular proliferation and cellular DNA rereplication but did not prevent cells from arresting in G(2). Our findings provide the first evidence to support the hypothesis that proteolytic cleavage of the E1(∧)E4 protein modifies its function. Also, different forms of the HPV1 E4 protein cooperate to negatively influence keratinocyte proliferation. We predict that these distinct biological activities of E4 act to support efficient amplification of the viral genome in suprabasal keratinocytes.